A two-factor model of the German term structure of interest rates - Jorge Barros Luís; Nuno Cassola (European Central Bank (ECB), 2001)
In this paper we show that a two-factor constant volatility model provides an adequate description of the dynamics and shape of the German term structure of interest rates from 1972 up to 1998. The model also provides reasonable estimates of the volatility and term premium curves. Following the conjecture that the two factors driving the German term structure of interest rates represent the H[-DQWH real interest rate and the expected inflation rate, the identification of one factor with expected inflation is discussed. Our estimates are obtained using a Kalman filter and a maximum likelihood procedure including in the measurement equation both the yields and their volatilities
Keywords: E43; G12; 330; affine model; expectations hypothesis; pricing kernels; term premiums